Ultrafast imaging of the Renner-Teller effect in a field-dressed molecule. Issue 9 (January 2020) - Amini, K; Steinle, T; Sclafani, M; Shaikh, M; Sanchez, A; Liu, X; Le, A T; Steinmetzer, J; Pfeiffer, T; Moshammer, R; Ullrich, J; Lewenstein, M; et al.
Synopsis: We present experimental results of linear-to-bent transition of field-dressed molecules, mediated by Renner-Teller effect. Using the state-of-the-art laser-induced electron diffraction (LIED) technique, we image a bent and symmetrically stretched carbon disulfide (CS2 ) molecule populating an excited electronic state under the influence of strong laser field. Our findings are well-supported by ab initio quantum mechanical calculations.